Fairies in colored pencil : learn to draw imaginative fairies in vibrant color - Archer, Lindsay; Burrier, Sara; Knox, Cynthia (Walter Foster, 2016)
Presents a sketchbook of various types of fairies, with step-by-step projects that guide artists from pencil sketch to full-rendered artwork, along with lessons in how to draw a range of physical characteristics, from facial features to wing types.